Bi(OTf)3-Catalyzed Three-Component Synthesis of Amidomethylarenes and -Heteroarenes - Schneider, Angelika E.; Manolikakes, Georg (Synlett, 2013)
A highly efficient Bi(OTf)3-catalyzed multicomponent synthesis of amidomethylated arenes and heteroarenes from readily available starting materials has been developed. This reaction proceeds under mild conditions, has a broad substrate scope, and in addition water is generated as only side product.
Keywords: multicomponent reactions; bismuth; green chemistry; acylimines; amidoalkylation